Greek-Turkish Relations: Problems and Prospects for Europe - Triantaphyllou, Dimitrios (Études helléniques / Hellenic Studies, 2004)
The protracted electoral campaign in Greece which ended with the elections of March 7, 2004, brought foreign policy back into the limelight. Greece's neighbourhood is saddled with a number of foreign policy issues which deserve close attention. More importantly, the future direction of Greek-Turkish relations will dominate the foreign policy agenda in the months and years to come. Greek-Turkish relations may also have an impact on the search for a settlement on Cyprus and the future of the island which will join the European Union in May 2004. Turkey's relations with the European Union are also coming to a head in December 2004 when the EU is expected to make a decision about the possible commencement of accession negotiations.